Implementasi Kebijakan Pengelolaan E-Retribusi Di Kota Bukittinggi - Handayani, Yesica; Ariany, Ria; Ameliza, Kiki (CV. ITTC INDONESIA, 2021)
The use of the e-retribution system in Bukittinggi since the beginning of 2020 has an effect on the local revenue (PAD) from the retribution sector. This study aims to find out and analyze the implementation of the Bukittinggi Mayor Regulation Number 39 of 2020 regarding the payment, deposit and payment procedures for wholesale and/or shop levies electronically analyzed using Edward III's theory. This research is a descriptive research with a qualitative approach. The types of data used in this study are primary data and secondary data. The data collection technique used was obtained by field research and library research. Data analysis was carried out by qualitative analysis and using purposive sampling technique in determining the sources. Testing the validity of the data is done by triangulation method. The results showed that the implementation of the electronic retribution collection policy at the Department of Small And Medium Business Cooperatives And Trade when viewed from the Eward III theory had not been implemented optimally. In terms of resources, there is a shortage of personnel in managing user fees electronically. In addition, the absence of specialized personnel in the field of information and technology has resulted in the slow development of the electronic levy receipt application system. The absence of a Standard Operating Procedure (SOP) made by the Department of Small And Medium Business Cooperatives And Trade is also an obstacle in implementing the policy. The e-retribution has not yet been implemented as a whole because the collection of retribution before 2019 is still collected manually.